An antibody precipitating urease and its possible relation to gastric ulcer. Issue 4 (December 1963) - Freisinger, F. S.
Abstract : An antibody precipitating urease was found in 171 out of 180 human sera. Data obtained on limited material (50 cases) suggest that the anti-urease titre is appreciably higher in the serum of patients suffering from gastric ulcer. This is a pointer towards a possible antigen-antibody mechanism in the genesis of chronic gastric ulceration.